Tat Twam Asi-Based Discussion on Developing English Business Proposal: A Case Study of Teaching Balinese Business Students - GDA Wicaksana; Yeni Suprihatin; Mar'an, Desy Awal; Dwi, Maharani Made Putri (English Language Education Study Program, 2025)
This study aims to analyze the implementation of Tat Twam Asi during teaching English business proposal on students in Institut Desain dan Bisnis Bali. This study is a qualitative study by collecting the data through observation checklist and interview guide. This study is highly valuable for the reference of promoting the Balinese culture and believe, especially Tat Twam Asi. The data was analyzed qualitatively by selecting and displaying the data in descriptive as well as drawing conclusion. The result shows that Tat Twam Asi is implemented as reflection of creating a proper flow of thinking which is easier for the students to develop their English business proposal.